A Higher Order Iterative Method for Computing the Drazin Inverse - F. Soleymani; Predrag S. Stanimirović (The Scientific World Journal)
A method with high convergence rate for finding approximate inverses of nonsingular matrices is suggested and established analytically. An extension of the introduced computational scheme to general square matrices is defined. The extended method could be used for finding the Drazin inverse. The application of the scheme on large sparse test matrices alongside the use in preconditioning of linear system of equations will be presented to clarify the contribution of the paper.